Polski system podatkowy a ochrona środowiska - Ptak, Michał (Polish tax system and environmental protection, 2007)
The paper analyzes the tax laws in Poland, which can be treated as instruments of environmental policy. These laws regulate State and local taxes and charges. Particular attention is paid to harmonization of energy taxation in the European Union and application of the minimum excise tax rates set by Directives of the EU. The paper presents the role of local self-govemment authorities which are entitled to specify rates of some taxes binding within their territory. By setting tax rates municipal councils can stimulate local environmental investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 450-459